2000
DOI: 10.1021/ja991074h
|View full text |Cite
|
Sign up to set email alerts
|

Size Scaling of Third-Order Off-Resonant Polarizabilities. Electronic Coherence in Organic Oligomers

Abstract: The variation of the nonlinear optical electronic polarizabilities of eight families of organic oligomers with molecular chain length is investigated using the coupled electronic oscillator (CEO) approach. Comparison of the saturation curves with contour plots of the first- and third-order density-matrix response shows a strong correlation between the magnitude of the saturation size, L s, and the antidiagonal size of the density matrix, L ρ, which constitutes a characteristic exciton size responsible for opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 35 publications
(59 reference statements)
5
71
0
Order By: Relevance
“…We observe nearly perfect linear scaling of state energies plotted as a function of the inverse number of π-electrons in the molecules. Such near-linear relationship is typical for a band-gap state in many conjugated polymers [285][286][287][288] and is not completely unexpected. A remarkable observation is that this scaling law holds for both e and e peaks corresponding to the higher-lying electronic states in molecules with and without substituents, and the slope of all curves is about the same.…”
Section: Scaling With Donor/acceptor Strength and Bridge Lengthmentioning
confidence: 64%
“…We observe nearly perfect linear scaling of state energies plotted as a function of the inverse number of π-electrons in the molecules. Such near-linear relationship is typical for a band-gap state in many conjugated polymers [285][286][287][288] and is not completely unexpected. A remarkable observation is that this scaling law holds for both e and e peaks corresponding to the higher-lying electronic states in molecules with and without substituents, and the slope of all curves is about the same.…”
Section: Scaling With Donor/acceptor Strength and Bridge Lengthmentioning
confidence: 64%
“…However, for conjugated systems composed of strongly interacting subunits, such as the polyenes and polyacenes considered in the present work, model calculations have shown that R increases supralinearly for small oligomers. [16][17][18][19]26,32,[86][87][88][89] Eventually, the rate of increase per subunit saturates, 19,21,25,26,86,88,90 but this occurs for systems significantly larger than those in the current study. The R iso of the polyenes, polyacenes, and their cations are plotted in Figures 2 and 3 as a function of system size.…”
Section: Resultsmentioning
confidence: 96%
“…10,11,18,51 For chain lengths larger than typically 2 nm, socalled saturation effects are observed, which means that λ max and γ per repeat unit converge to finite values that are sensitively dependent on the chemical structure and conformation of the polymer. [52][53][54][55][56][57][58][59][60] However, it was noted recently that the twophoton absorption coefficient of thin films of a polydiacetylene can still increase with M w , even if M w is significantly larger than the saturation limit of γ per repeat unit. 61 This behavior was attributed to chain ordering effects in thin films which can have strong impact on the third-order nonlinear optical properties of thin films of conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%